Effects of Hamamelis virginiana L. Extracts on Pseudomonas aeruginosa Growth and Antagonism of Ciprofloxacin - Cheesman, Matthew J; R Alcorn, Sean; Cock, Ian E (Pharmacognosy Communications)
Introduction: Pseudomonas aeruginosa is a Muti-Drug Resistant (MDR) pathogen that causes a myriad of infectious diseases. Limited evidence exists for antibacterial properties of extract preparations from the Virginian witch hazel (WH; Hamamelis virginiana L.; family: Hamamelidaceae) and their interactions with conventional antibiotics, especially against this significant pathogen. Materials and Methods: Five solvents of varying polarity were used to prepare WH extracts that were dried and resuspended in aqueous solution (1% DMSO) for testing in agar disc diffusion and liquid microdilution MIC assays. Results: The water extract showed mild (but statistically insignificant) P. aeruginosa growth inhibition, whilst the methanolic extract produced significant inhibition on agar and an MIC value in broth assays of 587 µg/mL. Extracts prepared with ethyl acetate, hexane and chloroform were inactive. Combinations of the active extracts with ciprofloxacin (the only antibiotic used in this study that was active against P. aeruginosa) produced an antagonistic effect on growth inhibition. Conclusion: WH extracted with polar solvents inhibit P. aeruginosa growth but counteract the activity of the antibiotic ciprofloxacin. Mechanisms of WH extract activity towards this pathogen, and their interaction(s) with ciprofloxacin, are discussed.
Keywords: Witch hazel; Pseudomonas aeruginosa; Extracts; Antibacterial; Antagonism; Traditional medicine